2020
DOI: 10.7860/jcdr/2020/45425.14248
|View full text |Cite
|
Sign up to set email alerts
|

The Poor and the Pandemic: COVID-19

Abstract: COVID-19 was proven to be a pandemic in early 2020 by the World Health Organisation (WHO). At present, 213 countries have been affected by the COVID-19 pandemic. In the history of global pandemics, COVID-19 has had a major impact on society as it has killed humans, spread human suffering and uprooted the lives of the people. Across the globe, there are 18,705,096 confirmed cases, 11,922,692 recovered cases, 704,385 deaths, and 6,078,019 active cases as of, 5 August 2020. It has affected the world’s economic, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Specifically, Hispanic, Black, and Indian Americans have more disproportionate COVID-19 incidents, hospitalization, and mortality than White people (Smith et al, 2021). Moreover, socioeconomic status also influences the impact of COVID-19 such that the poor are likely to experience more difficulties during COVID-19 (Raut et al, 2020). Future research may take ethnicity and socioeconomic status into consideration when studying the psychological impact of COVID-19 on people.…”
Section: Limitationsmentioning
confidence: 99%
“…Specifically, Hispanic, Black, and Indian Americans have more disproportionate COVID-19 incidents, hospitalization, and mortality than White people (Smith et al, 2021). Moreover, socioeconomic status also influences the impact of COVID-19 such that the poor are likely to experience more difficulties during COVID-19 (Raut et al, 2020). Future research may take ethnicity and socioeconomic status into consideration when studying the psychological impact of COVID-19 on people.…”
Section: Limitationsmentioning
confidence: 99%
“…A number of studies related to Covid pandemic were reported [28][29][30]. Some of the related studies were reviewed [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It is more vital that we raise awareness about this condition and educate people about it rather than spreading rumours with a political3 intent. Because the disease has not been eradicated, we must continue to observe the fundamental principles of wearing a face mask, using sanitizers, washing hands, and maintaining social distance [13][14][15]. By keeping these things in mind, we will one day be able to overcome this sickness together.…”
Section: Discussionmentioning
confidence: 99%